2016
DOI: 10.1021/jacs.6b02590
|View full text |Cite
|
Sign up to set email alerts
|

Cs[H2NB2(C6F5)6] Featuring an Unequivocal 16-Coordinate Cation

Abstract: Cesium bis(perfluoro-triphenylborane)amide, Cs[H2NB2(C6F5)6] (1), has been prepared by the reaction of sodium salt and CsF in dichloromethane and water. The compound is exceptional for a [H2NB2(C6F5)6](-) salt in that it contains a monatomic solute-free cation. Determination of the molecular structure revealed a novel C2 symmetrical conformation of the weakly coordinating [H2NB2(C6F5)6](-) anion, which gives rise to an unprecedented 16-coordinate (CN 16) Cs(+) cation in a likewise unprecedented tetracosahedral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 72 publications
(38 reference statements)
3
9
0
Order By: Relevance
“…This has been seen very recently in the experimental work of Pollak et al, [2] who found 16 Cs···F contacts in Cs[H2NB2(C6F5)6], and that by Popov et al in CoB16 -, [3] and has also been predicted theoretically by Gu et al [4] for M@Li16 (M = Ca, Sr, Ba, Ti, Zr and Hf). The record for the actinide elements stood at 14 for many years (in U(BH4)4), [5] but is now 15, established experimentally by Daly et al for Th(H3BNMe2BH3)4, [6] although the same authors used density functional theory (DFT) to predict that in the gas phase the number of Th···H contacts could rise to 16. All of these contributions make reference to the work of Hermann et al [7] who, in 2007, published in this journal a DFT survey of the geometric structures of Pb 2+ coordinated by He atoms.…”
supporting
confidence: 60%
“…This has been seen very recently in the experimental work of Pollak et al, [2] who found 16 Cs···F contacts in Cs[H2NB2(C6F5)6], and that by Popov et al in CoB16 -, [3] and has also been predicted theoretically by Gu et al [4] for M@Li16 (M = Ca, Sr, Ba, Ti, Zr and Hf). The record for the actinide elements stood at 14 for many years (in U(BH4)4), [5] but is now 15, established experimentally by Daly et al for Th(H3BNMe2BH3)4, [6] although the same authors used density functional theory (DFT) to predict that in the gas phase the number of Th···H contacts could rise to 16. All of these contributions make reference to the work of Hermann et al [7] who, in 2007, published in this journal a DFT survey of the geometric structures of Pb 2+ coordinated by He atoms.…”
supporting
confidence: 60%
“…Regardless of any scheme or table, cesium appears an outlier—one that binds through the outer core, with a free electron to boot. It recently broke the record for highest coordination number, 16, in a confined tetracosahedral arrangement of F atoms . And we sense it will feature in many new interesting molecules and materials.…”
Section: Figurementioning
confidence: 95%
“…It recently broke the record for highest coordination number,1 6, in ac onfined tetracosahedral arrangement of Fa toms. [22] And we sense it will feature in many new interesting molecules and materials.…”
Section: This Additional Electron With Respect To [Cso 4 ]mentioning
confidence: 99%